Tensile properties and microstructure of rheo-diecast 7075 alloy prepared by serpentine channel process - Wei-min Mao1; Wen-zhi Zhu1,2 (China Foundry, 2019)
A semisolid slurry of 7075 aluminum alloy was prepared by means of a serpentine channel process (SCP) and rheo-diecasting. The influences of pouring temperature during slurry preparation, the injection pressure and die preheat temperature on the mechanical properties and microstructure of a rheo-diecast 7075 aluminum alloy were investigated. The results show that the as-cast strength and elongation of the tensile samples were 210-260 MPa and 0.2%-1.7%, respectively, with an injection pressure of 130 MPa, a pouring temperature of 700-720 ºC, a preheat temperature of 280-350 ºC, and a plunger speed of 0.5 m·s-1. The results also show that the aged strength and elongation of the tensile samples were 420-453 MPa and 1.0%-1.4%, respectively, when the alloy solution was treated at 470 ºC for 12 h and aged at 120 ºC for 24 h. The substantial shrinkage porosity in the 7075 aluminum alloy tensile samples was the main cause of low elongation.